Optical dating of an offset river terrace sequence across the Karakax fault and its implication for the late Quaternary left-lateral slip rate. (1st October 2017) - Gong, Zhijun; Sun, Jimin; Zhang, Zhiliang; Fu, Bihong; Jia, Yingying
Graphical abstract: Highlights: A set of terraces are cut and left-laterally offset by the Karakax fault. The OSL dating can be well applied to terraces along the Karakax valley. The slip rate of the Karakax Fault was ∼7.8 mm/yr during the late Quaternary. Abstract: The Karakax fault is one of the largest left-lateral strike-slip faults at the rim of the northwestern Tibetan Plateau. In this study, the optical dating techniques were applied to the Taersayijilega river terraces, which were transversely cut and offset by the Karakax fault. Six fluvial sand samples from the river terraces were collected and dated. The results show that the terraces (T2-T5) have ages of 14.5 ± 1.0 ka, 21.2 ± 1.2 ka, 28.5 ± 1.7 ka and 39.7 ± 2.5 ka, respectively. By interpreting high resolution satellite images, the horizontal displacements of the four river terraces are estimated at ∼160 m, ∼235 m, ∼260 m and ∼365 m, respectively. Based on the ages and offsets of the terraces, the average left-lateral slip rate of the Karakax fault was estimated at 7.8 ± 1.6 mm/a during the late Quaternary. Such rate of the Karakax fault is significantly higher than that of the Longmu-Gozha Co fault, suggesting that the Karakax fault plays an important role in accommodating eastward movement of the Tibetan Plateau at the northwest during the late Quaternary.